1960
DOI: 10.1039/jr9600004413
|View full text |Cite
|
Sign up to set email alerts
|

856. Syntheses of perhydroanthracenes involving the reduction of thioketals with lithium and ethylamine. The synthesis of 1,4,4aα,5,8,8aβ,9,9aβ,10,10aα-decahydroanthracene

Abstract: The unsaturated diketones (I) and ( 11) have been converted in good yields into the corresponding perhydroanthracencs by reduction of their bis(ethy1ene dithioketals) with lithium and ethylsmine. A diem (XIII) required for the study of its addition reactions has been synthesised. ALDER and STEIN^ first condensed P-benzoquinone with butadiene (2 mol.) to give a product that they regarded as the diketone (I) or its stereoisomer with all-&-bridgehead hydrogen atoms. We show below that this adduct has the structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1964
1964
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…We also tried to reduce VII with sodium in liquid ammonia [10] and tosylhydrazone XXI with LiAIH 4 [II]. Both these compounds yielded XIX as the sole product in a 30-35% yield.…”
Section: XXImentioning
confidence: 99%
See 2 more Smart Citations
“…We also tried to reduce VII with sodium in liquid ammonia [10] and tosylhydrazone XXI with LiAIH 4 [II]. Both these compounds yielded XIX as the sole product in a 30-35% yield.…”
Section: XXImentioning
confidence: 99%
“…We tried to prepare the [10] annulene quinone (XXIX) [2a, 18]. Reaction of IV with one equivalent of perbenzoic acid yielded the Bayer-Villiger oxidation product, i.e., the keto-lactone XXXI, instead of the monoepoxy diketone XXX (Chart 3).…”
Section: XXImentioning
confidence: 99%
See 1 more Smart Citation
“…Isomerization of the cis-anti-cis isomer of the butadiene-p-benzoquinone bisadduct with alkali6 is known to yield the trans-syn-trans isomer. 4 It cannot be concluded from this that the isobisadduct lb of the present study has the same configuration. However, a comparison of the melting points in the hydroanthraquinone and hydrodibenz [a,/i]anthraquinone series and their hydrogenation products is of interest.…”
mentioning
confidence: 55%
“…Crossley and Henbest reported that Li/liquid ammonia can be replaced by Li/EtNH 2 for the electron‐mediated desulfurization of thioketals of perhydroanthracenes . This protocol produced the methylene compounds in good yields did not affect the stereochemistry of the bridge head positions.…”
Section: Desulfurization Of Thioacetals Using Metalsmentioning
confidence: 99%